Pembelajaran Kitab Fathul Qorib dalam Meningkatkan Pengetahuan Santri Tentang Fiqh di Pondok Pesantren Nurun ‘Ala Nur 2 Kepencar Wonosobo - Arum Wigatiningtyas; Robingun Suyud El Syam; Asep Sunarko (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Pesantren is basically a traditional Islamic educational dormitory where the students live and live together to study Islamic religious knowledge under the auspices of the kyai. The book Fathul Qorib is one of the Islamic boarding school literature books in the field of Shafi'i school of jurisprudence by Ibnu Qasim Al-Ghazzi. Fiqh exists as an answer to everyday human problems related to actions and worship. Where there are still many students who make mistakes in implementing their daily worship which is not in accordance with the Shari'a. In its application, the methods used are the wetonanan, sorogan and bandongan methods. This research uses field research using a qualitative approach. There are 3 data collection techniques used, namely observation, interviews and documentation. There are 2 data sources that will be used, namely primary data and secondary data. There are three data analysis techniques used, namely data reduction, data presentation and drawing data conclusions. The process of learning the book of Fathul Qorib in increasing students' understanding of Fiqh at the Nurun 'ala Nur 2 Kepencar Wonosobo Islamic boarding school uses the wetonan method with discussion. The Process of Learning the Book of Fathul Qorib in Improving the Translating Ability of Santri at the Nurun 'ala Nur 2 Kepencar Wonosobo Islamic Boarding School using the sorogan, wetonan and direct test methods during evaluation.